Implementasi Kegiatan Unit Kegiatan Kerohanian dalam Pembinaan Akhlak Mahasiswa Universitas Negeri Padang - Eka Satriani; Wirdati Wirdati (Prodi Pendidikan Keagamaan Islam, 2022)
This research focuses on fostering student morals, namely UKK (Unit Kegiatan Kerohanian). To find the form and process of implementing UKK programs. Using a research method descriptive approach, all data were using interviews with 20 informants selected using data techniques, the authors also took data through interviews, documentation, and observation. All data is then analyzed by thematic method and document analysis. The results of the study there are 7 fields, 2 divisions, and 47 work programs, the fields: Daily management board, Cadreization, Network Public, Al Qur’an, Media, Muslim Affairs, Entrepreneurship, and Secretarial Division. Implementation of UKK activities The implementation of the UNP UKK work program, the field of the Daily Management Board in the field of managing and directing all fields of organized work programs, namely, LDK Training provides training for new LDK administrators. Tasqif, discussions and ustadz the hadith the Qur'an, faith, the science of interpreting hadith and Qur'an, the history Nabi SAW.